POTATO BASED INTENSIVE CROPPING SYSTEMS FOR NILGIRIS - Manorama, K; Lal, S. S; Krishna Prasad, K. S. (Potato Journal, 2013)
To improve the cropping intensity of Nilgiris region, trials were conducted during 2003 and 2004 summer seasons at Muthorai with various inter crop combinations. During 2003, three intercrops, viz., wheat, french beans and maize were tried with seven, nine and nine treatments, respectively under three different trials. Considering the performance of different intercrops during 2003, a trial was planned during summer, 2004 with wheat, French beans and maize as intercrops in potato. The treatments include three combinations each of intercrops and all the four pure crops totaling to 13. The potato equivalent yield was highest in potato + french beans intercropping when sown in 75 : 50 proportions followed by the treatment, potato + frenchbeans at 50 : 50 proportions. The net revenue of the same treatments i.e., potato + french beans at 75 : 50 and 50 : 50 proportions was higher i.e., Rs. 70,055/ -and Rs. 65,820/-per ha as compared with other combinations. Although potato + maize performed better at 75 : 50 proportions, but due to longer duration of maize in this area, it can not be considered as a profitable proposition. Hence, potato + french beans at 75 : 50 is the most suitable intercrop combination for the Nilgiris region. It also improved the soil fertility status by improving the organic carbon status as well as available P and K content of the soil.